Lithuania ‐ Belarus economic relations: How the EU accession impacted bilateral trade - Ginevičius, Romualdas; Tvaronavičienė, Manuela; Korsakienė, Renata; Kalaūinskaitė, Kristina (Journal of Business Economics and Management, 2007)
Lithuania among other 10 Central and Eastern European countries joined the European Union on 1 May 2004. A lot of forecasts about transformations in international trade relationships had been discussed; overall shift towards the EU had been expected. The paper aims to verify what actual effect newly imposed trade regulations have. Presented elaboration of discussed issue would be performed in the following sequence. At first, trade structure by product groups of trade between Lithuania and Belarus in the years 2000 and 2005 would be juxtaposed. Volumes of import and export would be considered respectively. Changes in trade regime would be taken into account. Adopted approach allowed us to trace which changes in trade regime impacted trade character and which not. First Published Online: 14 Oct 2010